cindy974
cindy974
19-04-2022
Mathematics
contestada
HELP!!!!!!!!!!!!!!!!!!!!!!
Respuesta :
palium
palium
19-04-2022
Answer = 1
If a + b - 3 = 0
then, a = 3 - b.
Let’s substitute it in the second expression.
(3 - b)^3 + b^3 + 9(3 - b)(b) - 26 = 27 - 27b + 9b^2 - b^3 + b^3 + 9(3b - b^2) -26 =
= 27 - 27b + 9b^2 + 27b - 9b^2 - 26 = 1
Answer Link
VER TODAS LAS RESPUESTAS ( 58+ )
Otras preguntas
HELP ASAP! An ice cube has _____ than a cup of hot tea. A)less heat energy B)more cold energy C)more heat energy D)less cold energy
Which affect do some believe third-party candidate Ross Perot had on the 1992 election?
Order from least to greatest, please.
Can someone help me with this
3000 for 3 years at 8% compounded quarterly
Students at Sugar land middle school were asked what their favorite sport was. The table below shows the results of the survey. If you select a student at rando
Which of the following ordered pairs represents an output of 5 and an input of -8? (-8,-8) (-8,5) (5, 5) (5, -8)
Which of the following is an example of the impact trade had on the people of Southern and Eastern Africa? A. Eastern Africans practiced the same religion as
SOLVE AND CHECK1) -2K + 7 = -32) 3M + 5 = 143) 11 = 1/3 A + 2 4) -4.5 = -0.15P
Simplify the product
ACCESS MORE